Digital Innovation as the Key to Efficiency and Accountability of Public Administration in Medan City, Indonesia - Sibuea, Nunti (Manunggal Halim Jaya, 2025)
Digital transformation has become an urgent need in public administration, especially in the city of Medan, to improve service efficiency and accountability. This study aims to analyze the influence of digital infrastructure and technological literacy on the efficiency and accountability of public administration. A quantitative approach with the Structural Equation Modeling (SEM) method was used to process data collected from 200 respondents, consisting of government officials and public service users. The results of the analysis show that digital infrastructure contributes significantly to administrative efficiency, while technological literacy plays an important role in increasing accountability. The main obstacles in the implementation of digital innovation include the lack of interoperability of information systems between agencies and the low digital literacy among certain communities. This research provides a comprehensive understanding of the importance of technology integration and human resource development in the digital transformation process of public administration. This finding is expected to be the basis for the formulation of policies and strategies to improve the quality of digital-based public services in the city of Medan.